Informed Consent in the Newly Established Biobank - Kinkorová, Judita; Topolčan, Ondřej; Kučera, Radek (International journal of environmental research and public health, 2019)
Informed consent is an important document for every existing biobank or repository to obtain, store and use human biospecimens and associated data and information for current and future research. Biobanks have undergone great progress worldwide during the last three decades and have become an integral part of personalized medicine and health care systems and due to new scientific and social questions to be solved. Ethical, legal and social issues (ELSI) guarantee safe sample and data management, and informed consent is one of the key ELSI documents. The form and the consent given in biobank informed consent forms differs between biobank-related institutions, national biobanks, between EU states, and to find the optimal informed consent requires one to fulfil national and international laws and regulations. The Biobank in Pilsen, Czech Republic was officially opened on April the 20th 2017 as a hospital-integrated biobank, and the informed consent was one of the essential documents that had to be ready prior the opening. The process of formulating informed consent corresponding with institutional, national, and international rules and laws to share the experience, to present the challenges, and to demonstrate the national dissimilarity are tasks of the article.
Keywords: Biological Specimen Banks; Informed Consent; personalized medicine; lidé; informed consent; informovaný souhlas pacienta; Czech Republic; banky biologického materiálu; Biobank; ELSI; Humans; Česká republika